The exchange rate and its impact on Pakistani exports: An ARDL approach - Ahmad, Sareer; Ali, Majid; Hussain, Ihsan Ullah (Journal of Management, Economics, and Industrial Organization, 2021)
Export is the backbone of healthy economies and Pakistan is the emerging economies of the South Asian region. This study examines the impact of the exchange rate on Pakistani exports using time series data from the period 1980 to 2018. Secondary data are taken from the central bank (State Bank of Pakistan) and WDI (World Development Indicators). Unit root and Phillips Peron test were used to check the stationarity of the variables while the ARDL model was applied to verify the relations between variables. The findings of the study demonstrated that the exchange rate has negative and insignificant relations with Pakistani exports. Exchange rate appreciation hurts the trade balance of Pakistan. The policy implication based on our findings is that heavy fluctuations in the exchange rate have limited importance, The trade balance is always a deficit in Pakistan because our exports are the primary product due to this market price charges are low. It indicates that only the exchange rate is not a fruitful option to boost the trade balance.
Keywords: exchange rate; ADF test; ARDL; exports